2011
DOI: 10.1111/j.1439-0507.2009.01766.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mutations in Erg11 gene of fluconazole resistant Candida albicans isolates from Turkish hospitals

Abstract: Widespread use of fluconazole has resulted in resistance in strains of Candida. The aim of our study was to investigate Y132H and other mutations in the ERG11 gene in conferring fluconazole resistance to C. albicans isolates. Seven fluconazole-resistant (R)/susceptible dose-dependent (SDD)/trailing and 10 fluconazole-susceptible (S) isolates were included. Restriction enzyme analysis was performed on all isolates for Y132H mutation and sequence analysis was performed for other mutations in the ERG11 gene. None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
2
25
1
4
Order By: Relevance
“…The E266D substitution was detected in 3 azole antifungal SDD strains (CHC95, CHC126 and CHC169). E266D probably does not contribute to azole resistance because it is found in both azole-resistant and azolesusceptible strains [5,27,28] . T123I substitution was found in two resistant isolates (CHC119 and CHC125) and it was also observed in two resistant isolates (C97 and C112) from Anhui in China [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E266D substitution was detected in 3 azole antifungal SDD strains (CHC95, CHC126 and CHC169). E266D probably does not contribute to azole resistance because it is found in both azole-resistant and azolesusceptible strains [5,27,28] . T123I substitution was found in two resistant isolates (CHC119 and CHC125) and it was also observed in two resistant isolates (C97 and C112) from Anhui in China [29] .…”
Section: Discussionmentioning
confidence: 99%
“…V437I substitutions occurred in one SDD isolate (CHC106), accompanied by other point mutations. Some studies have reported the occurrence of the V437I mutations in both azole-susceptible and azole-resistant isolates [12,26,28] . The A114V substitution was found in one fluconazole-resistant strain (CHC114).…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce Manastır ve arkadaşlarının 9 aynı C.albicans suşları ile yaptığı bir çalışmada, ERG11 geni mutasyonları araştırılmış olup, FLU'ya direnç gelişiminde rolü olduğu bildirilmiş K143R, G464S, G465S ve V488I ile dirençte rolü kesin olmayan D116E, D153E, E266D, S412T ve R469K mutasyonları saptanmıştır. Araştırmamızda, H1, H2, B suşla-rında K143R ve V488I mutasyonuna ek olarak CDR1/2, MDR1 fazla ekspresyonunun; H3 suşunda G464S, G465S mutasyonu ile birlikte CDR1/2 fazla ekspresyonunun FLU direncinde rolü olduğu görülmüştür.…”
Section: Discussionunclassified
“…İnceleyebildiğimiz kadarıyla, Türkiye'de C.albicans izolatlarında FLU direnç mekanizmalarına ilişkin yayınlanan tek çalışma, bu suşlarda ERG11 genindeki nokta mutasyonlarının incelendiği araştırma 9 olup, bu araştırmamız ise önceki çalışmayı tamamlar niteliktedir. Bu veriler ışığında, çalışmaya alınan FLU-R C.albicans suşlarında, ERG11 genindeki K143R, G464S, G465S ve V488I mutasyonları 9 ile birlikte CDR1, CDR2 ve MDR1 fazla ekspresyonlarının dirençten sorumlu önemli mekanizmalar olduğu sonucuna varılmıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation